Composition and antioxidant analysis of jiaosu made from three common fruits: watermelon, cantaloupe and orange. Issue 1 (1st January 2021) - Jiang, Kangkang; Zhao, Yunlin; Liang, Cheng; Xu, Zhenggang; Peng, Jiao; Duan, Choucang; Yang, Guiyan
ABSTRACT: Jiaosu, also called as fermented fruit and vegetable juices, is becoming an increasingly popular health food, especially in East Asian markets. Watermelon, cantaloupe and orange were used as the raw materials to produce five kinds Jiaosu with natural fermentation, including single source Jiaosu and mixed jiaosu. Then the composition and antioxidant capacity were determined. All Jiaosu appear brown and different Jiaosu vary greatly. The pH of five kinds Jiaosu range from 3.06 to 4.55. Between the five kinds Jiaosu, orange Jiaosu is the highest in total protein (9.46 ± 0.41 mg/ml), total phenol (0.32 ± 0.01 μg/ml) and alcohol (56.51 ± 0.03 μg/ml). All Jiaosu have strong antioxidant capacity and watermelon Jiaosu shows the strongest antioxidant capacity. The antioxidant capacity of five kinds Jiaosu determined by FRAP assay is significantly correlated with the total protein content and total phenol content, respectively. The results indicated the raw materials had a decisive effect on the components and antioxidant capacity of Jiaosu.